Current capabilities of ultrasound tomography for evaluation of the depth of myometrial invasion and its transfer to the cervix in patients with cancer of the uterus - M. A. Chekalova; M. N. Kolpakova; V. M. Nechushkina (Опухоли женской репродуктивной системы)
With the purpose of studying opportunities of modern ultrasound technologies in diagnostics of an endometrial carcinoma we survey 33 patients. It was revealed high information value of ultrasound for definition of depth of uterus cancer invasion. At carrying out of ultrasonic research the complex of the following techniques two-dimensional/three-dimensional ultrasound in the В mode, Color and Power coding, sonoelastography, spectral Doppler analysis was used. Use sonoelastography, ultrasound in a combination to an wide spectrum modern Doppler techniques allows to solve the broad audience of problems in frameworks for intronozologycal diagnostics of an endometrial carcinoma: to determineprecise localization of a tumor in a cavity of a uterus; volume of the primary tumoral center; depth invasion in myometrium; transition of tumoral process on cervical canals. Sonoelastography is the modern method for a comparative analysis of the density and compressibility of tissues, and it can be an additional diagnostic test for diagnostic test to define of local prevalence of the tumor. It is very important for surgeons to determine an adequate volume of operation.